2006
DOI: 10.1111/j.1440-1681.2006.04367.x
|View full text |Cite
|
Sign up to set email alerts
|

Naringin Does Not Alter Caffeine Pharmacokinetics, Energy Expenditure, or Cardiovascular Haemodynamics in Humans Following Caffeine Consumption

Abstract: 1. Naringin, a grapefruit constituent interacts with many medications including caffeine, a popular weight loss supplement. The purpose of the current study was to identify changes in caffeine pharmacokinetics, resting energy expenditure (REE), oxygen consumption (VO(2)) and respiratory exchange ratio (RER) after an acute dosage of caffeine and naringin. 2. Using a double-blinded, counterbalanced design, REE, VO(2), and RER were measured before and systematically for 8 h after a single dosage of caffeine (CAF,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Although a 13% increase in AUC was observed, the difference was of no statistical significance (n ¼ 10). In addition, the pharmacokinetic profiles and parameters for caffeine were not significantly different after co-administration with naringin (Ballard et al, 2006), an important constituent of grapefruit juice (n ¼ 10). Two studies have been published on the pharmacokinetic impact of grapefruit juice on theophylline, another classical CYP1A2 substrate.…”
Section: Discussionmentioning
confidence: 91%
“…Although a 13% increase in AUC was observed, the difference was of no statistical significance (n ¼ 10). In addition, the pharmacokinetic profiles and parameters for caffeine were not significantly different after co-administration with naringin (Ballard et al, 2006), an important constituent of grapefruit juice (n ¼ 10). Two studies have been published on the pharmacokinetic impact of grapefruit juice on theophylline, another classical CYP1A2 substrate.…”
Section: Discussionmentioning
confidence: 91%
“…Although caffeine is being researched in a variety of areas regarding human health the focus of this review will be on its potential as an aid in weight loss, thus reducing the overall risk for developing the metabolic syndrome (Ballard and others 2006; Fujioka and others 2006). The metabolic syndrome is a significant and growing health concern affecting approximately 25% of the United States population (Ford and others 2002; Zimmet and Alberti 2008).…”
Section: Caffeine Consumption and Human Healthmentioning
confidence: 99%
“…Energy balance is the main determinant of weight regulation. In this context, research on caffeine has demonstrated its role in increasing metabolic rate, energy expenditure (EE), lipid oxidation, and lipolytic and thermogenic activities; all favorable components in regards to weight management and possible weight loss in humans (Acheson and others 2004; Ballard and others 2006; Dallas and others 2008). Although the role of thermogenic activity in weight control is in the process of being analyzed, multiple studies have shown that caffeine can influence energy balance in humans.…”
Section: Caffeine Consumption and Human Healthmentioning
confidence: 99%
“…Naringin also inhibits various CYP isoenzymes, thus increasing the bioavailability of calcium channel blockers such as verapamil [40] via CYP3A4 and paclitaxel via CYP3A1/2 inhibition [41]. Nevertheless, naringin has also been shown to have no effect on the pharmacokinetics of drugs such as doxorubicin [42] and caffeine [43].…”
Section: Drug Interactions !mentioning
confidence: 99%